2021
DOI: 10.20473/jebis.v7i1.24998
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration and Strengthening of Sharia Financial Inclusion Through Merging Sharia Banking in Indonesia

Abstract: Islamic banking in Indonesia is slowly experiencing significant developments both in terms of number of assets and its financial performance. On the other hand, the market share was only able to grow by 6.18 percent with grow rate less than 5 percent. Therefore, one of the strategies to increase and accelerate the growth of Islamic banking is through a merger. The purpose of this study is to provide an overview of the potential development of Islamic banking after the merger as an effort to strengthen the incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This statement also strengthens the opinion of Goeltom (2009) which states that the expansion of Islamic banking also contributes to the growth of the real sector, because Islamic financing is closely related to the development of the real sector. The growth of Islamic banking also causes increased competition in the financial sector, because local banks seek to increase the scale of their assets through mergers and acquisitions, so that this increasingly fierce competition has an impact on the quality of banking services getting better and the range of Islamic banking products wider (Syarifuddin et al, 2022). Apart from that, the development of Islamic banking in Indonesia is a manifestation of a society that really needs a financial system, especially Islamic banking products and services that are healthy and meet sharia standards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This statement also strengthens the opinion of Goeltom (2009) which states that the expansion of Islamic banking also contributes to the growth of the real sector, because Islamic financing is closely related to the development of the real sector. The growth of Islamic banking also causes increased competition in the financial sector, because local banks seek to increase the scale of their assets through mergers and acquisitions, so that this increasingly fierce competition has an impact on the quality of banking services getting better and the range of Islamic banking products wider (Syarifuddin et al, 2022). Apart from that, the development of Islamic banking in Indonesia is a manifestation of a society that really needs a financial system, especially Islamic banking products and services that are healthy and meet sharia standards.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it can be concluded that the stimulus of Islamic banks continues to have a positive influence on the development of the national economy, which is also accompanied by improvements in the quality of products and services (Syarifuddin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%